Anaerobic Co-Digestion Effluent as Substrate for Chlorella vulgaris and Scenedesmus obliquus Cultivation - Paolina Scarponi; Alessandro Bonetto; David Bolzonella; Sergi Astals; Cristina Cavinato (Energies, 2020)
Anaerobic digestate supernatant can be used as a nutrient source for microalgae cultivation, thus integrating phytoremediation processes with high value products storage in microalgae biomass. Microalgae are able to use nitrogen and phosphorous from digestate, but high nutrient concentration can cause growth inhibition. In this study, two microalgae strains (C. vulgaris and S. obliquus) were cultivated on the anaerobic co-digestion supernatant (obtained from the organic fraction of municipal solid waste (OFMSW) and waste activated sludge (WAS)) in a preliminary Petri plate screening at different dilutions (1:10 and 1:5) using a synthetic medium (ISO) and tap water (TW). Direct Nile red screening was applied on colonies to preliminarily identify hydrophobic compound storage and then a batch test was performed (without air insufflation). Results show that C. vulgaris was able to grow on digestate supernatant 1:5 diluted, while Nile red screening allowed the preliminary detection of hydrophobic compound storage in colonies. The analysis carried out at the end of the test on ammonia, phosphate, nitrate and sulphate showed a removal percentage of 47.5 ± 0.8%, 65.0 ± 6.0%, 95.0 ± 3.0% and 99.5 ± 0.1%, respectively.